2022
DOI: 10.1302/2046-3758.114.bjr-2021-0169.r1
|View full text |Cite
|
Sign up to set email alerts
|

Does tibial design modification improve implant stability for total knee arthroplasty? An experimental cadaver study

Abstract: Aims One of the main causes of tibial revision surgery for total knee arthroplasty is aseptic loosening. Therefore, stable fixation between the tibial component and the cement, and between the tibial component and the bone, is essential. A factor that could influence the implant stability is the implant design, with its different variations. In an existing implant system, the tibial component was modified by adding cement pockets. The aim of this experimental in vitro study was to investigate whether additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…22 In 2017, DePuy launched a modified tibial component (attUne s+) incorporating backside grooves with the aim of facilitating interdigitation of the cement to improve fixation. 57 However, an estimated 600,000 tKas were implanted before this change of design. 7 Furthermore, the rest the design remained the same and there is currently little clinical evidence that these changes have influenced the rates of RLL formation.…”
Section: Discussionmentioning
confidence: 99%
“…22 In 2017, DePuy launched a modified tibial component (attUne s+) incorporating backside grooves with the aim of facilitating interdigitation of the cement to improve fixation. 57 However, an estimated 600,000 tKas were implanted before this change of design. 7 Furthermore, the rest the design remained the same and there is currently little clinical evidence that these changes have influenced the rates of RLL formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified prosthetic debonding as a concern, as some tibial implants have ineffective strand locks at the prosthesis-bone cement interface, resulting in postoperative implant failure [ 25 27 ]. In an effort to address this issue, Jaeger et al [ 28 ] conducted a cadaver study, implanting a tibial component with and without additional cement pockets in 15 fresh-frozen human leg pairs. The authors found that the additional cement pockets were biomechanically advantageous, improving the fixation performance of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the specimens were cast in a mold using synthetic resin (Rencast FC 53, Huntsman Advanced Materials GmbH, Germany), in order to secure the specimens into the material testing machine. For the assessment of implant stability, an incremental dynamic load was applied at 1 Hz for the axial force with simultaneous extension-flexion between 20° and 50°, as had been done in a prior study [ 28 ]. The load maxima occurred at the time of extension and flexion, respectively [ 29 ].…”
Section: Methodsmentioning
confidence: 99%